Identifying Molecular Markers of Successful Graft Union Formation and Compatibility - Loupit, Grégoire; Cookson, Sarah Jane (Frontiers in Plant Science, 2020)
Grafting is a technique used for millennia for vegetative propagation, especially in perennial fruit crops. This method, used on woody and herbaceous plants, can improve several agronomic characteristics, such as yield or vigor, as well as tolerance to biotic and abiotic stresses. However, some scion/rootstock combinations suffer from poor graft compatibility, i.e., they are unable to form and/or sustain a successful graft union. Identifying symptoms of graft incompatibility is difficult because they are not always present in the first years after grafting and in most cases the causes of incompatibility are still poorly understood. Studies of changes in transcript abundance during graft union formation indicate that grafting responses are similar to responses to wounding and include the differential expression of genes related to hormone signaling, oxidative stress, formation of new vascular vessels, cell development, and secondary metabolites, in particular polyphenols. This review summarizes current knowledge of the changes in transcript abundance, redox status and metabolites accumulation during graft union formation and in cases of graft incompatibility. The goal of this review is to discuss the possibility of identifying marker transcripts, enzyme activities and/or metabolites of grafting success and graft compatibility which could be used to score grafting success for genetic research and in breeding programs. We highlight gaps in current knowledge and potential research directions in this field.